186k views
14 votes
Write your answer with no space and any fraction with “/“

Write your answer with no space and any fraction with “/“-example-1

1 Answer

6 votes

Answer:

y + 3 = -½(x - 1)

Explanation:

Point-slope form equation is given as y - b = m(x - a), where,

m = slope, and (a, b) is a point the line passes through.

Given that the line is perpendicular to the y = 2x - 1, the slope (m) will be the negative reciprocal of 2, which is -½.

Thus, substitute m = -½, a = 1, and b = -3 into y - b = m(x - a).

Thus:

y - (-3) = -½(x - 1)

y + 3 = -½(x - 1)

User Oriana
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.